2021
DOI: 10.1111/jocn.15612
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' competence in stroke care pathways: A mixed‐methods systematic review

Abstract: Background The challenges of caring for stroke patients are growing due to population ageing and improved survival rates. Healthcare professionals' competence development in stroke care is a necessity to ensure high‐quality patient care. Objectives To identify and describe the competence areas of healthcare professionals working in the stroke patient care pathway and factors influencing these competences. Design A mixed‐methods systematic review. Methods The review was conducted according to the JBI guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…The presented results strongly support the claim that nurses play a vital role in stroke care, which has been suggested in previous studies [25]. Doctors were part of the intervention planning group; however, in the future, lifestyle counselling interventions should be more tailored to a multidisciplinary team of stroke professionals [25]. This type of approach would promote both support from doctors as well as long-term adherence to treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The presented results strongly support the claim that nurses play a vital role in stroke care, which has been suggested in previous studies [25]. Doctors were part of the intervention planning group; however, in the future, lifestyle counselling interventions should be more tailored to a multidisciplinary team of stroke professionals [25]. This type of approach would promote both support from doctors as well as long-term adherence to treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Earlier studies also suggest that certain elements of the counselling provided during the acute hospitalisation phase, such as interactions [13,21], and the resources of health-care personnel, are connected to later adherence to a healthier lifestyle [13]. The healthcare professionals who counsel stroke patients about self-management strategies need to have versatile competences [25]. Earlier research has investigated how nurseled lifestyle counselling interventions affect adherence to lifestyle changes [5,[26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a systematic review synthesised a total of 20 papers [16], and 16 papers [17] on nursing-related research paper among these only one mixedmethods paper was identified. Worse, a further two mixedmethods review recently revealed that out of 48 [18,19] synthesised nursing research papers, not one single mixedmethods paper was identified. This clearly depicts that mixedmethods research is still in its infancy stage in nursing but we can say there is huge scope to implement it to understand research questions on both sides of coin [4].…”
Section: The Relevance Of Mixed-methods In Health Researchmentioning
confidence: 99%
“…Nurses are the medical personnel that see the full impact of a stroke and should be equipped with the ability to help patients recover more quickly (Allsassmah, 2020). Jarva et al (2021) stressed the importance of multidimensional competence in nurses' work in stroke units, defining nursing competency as the mix of skills, knowledge, and attitudes required for successful or outstanding performance. In order to offer high-quality care and assist patients in achieving the best possible results, nurses in stroke care units must have relevant information, competent abilities, and a positive attitude.…”
Section: Effectiveness Of An Interventional Program On Nurses' Knowle...mentioning
confidence: 99%